Analisis karya tulis ilmiah Pusat Penelitian Geoteknologi LIPI tahun 2010-2018 - Didik Prata Wijaya; Abdurrakhman Prasetyadi (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Preliminary. Research products in the form of scientific papers (KTI) at the Research Center for Geotechnology-LIPI continue to grow in quality and quantity, so it is necessary to analyze and study the scientific works to reveal the extent to which KTI is contributing to the Research Center for Geotechnology. Research methods. The research method used is descriptive with the bibliometric approach. Data collection was obtained from annual reports from 2010-2018. Analysis data. The data that has been collected is then analyzed descriptively using Ms. Excel software to facilitate the distribution and visualization of data. Results and Discussion. The results of this study note that KTI published by researchers at the Research Center for Geotechnology is scattered in various national/international journals, national/international proceedings, and books/potpourri. The highest KTI issued was national proceedings, totaling 343 titles. The second position is occupied by international journals with 182 titles. Third, there are 104 national journals. The last international proceedings with 92 titles and 67 books. Indonesian is the most widely used language, as many as 542 articles and male gender dominates as many as 1946 researchers. While the year in which there was one highest type of scientific papers published was 2014 with 63 national proceedings. Conclusions and recommendations. This research has described the distribution of KTI Center for Geotechnology, where KTI is the most dominant national proceeding and the least possible international journal due to the level of difficulty.